Which Policies Can Reduce the Cost of Capital in Southern Africa ? - Grandes, Martin (OECD Publishing, 2004)
. Lowering interest rates and, thus, the cost of borrowing in the rand zone (Lesotho, Namibia, Swaziland and South Africa) is a priority to promote investment and economic growth. . Local-currency interest rates in these countries are driven by those on rand-denominated transactions. Reducing the level and volatility of the rand premium would help reduce ?nancing costs in the region. . Policies should promote: enhancing ?nancial-market liquidity; easier access to South African ?nancial markets for African entities; domestic saving capacity; and the improvement of international perception of the rand. . Johannesburg could become a ?nancial "hub" for the region, channelling cheap resources to its neighbours
Keywords: Development